Identifikasi Dampak Sosial Ekonomi Pada Berbagai Program Terkait Intensifikasi Pertanian Padi Di Lahan Pasang Surut Sumatera Selatan - Dessy Adriani; M. Huanza; Dini Damayanthy (Program Studi Agribisnis Universitas Sumatera Selatan, 2022)
Utilization of tidal land to support food security requires agricultural intensification, related to the limited ecological conditions. Technical research related to agricultural intensification in tidal land has been carried out, but the socio-economic aspects related to it have not been widely studied. This research is a quantitative research with survey research techniques. The research was carried out in 2017 in Banyuasin Regency and Musi Rawas Regency with a sample of 211 out of 1083 farmers applying various types of agricultural intensification. The results of this study was pointed that intensification has a negative impact on the allocation of working time and unemployment, but has a positive impact on income and productivity.